ByzRev 06.2024.068: Konstantin M. Klein – Johannes Wienand (eds), City of Caesar, City of God: Constantinople and Jerusalem in Late Antiquity (Millennium Studies 97).: Berlin – Boston: De Gruyter 2022. - Olshanetsky, Haggai (The Byzantine Review, 2024)
Konstantin M. Klein – Johannes Wienand (eds), City of Caesar, City of God: Constantinople and Jerusalem in Late Antiquity (Millennium Studies 97). Berlin – Boston: De Gruyter 2022. xvi, 349 pp. – ISBN 978-3-11-071720-4.